The Ten Commandments - Hardwicke, Cedric; 1893-1964.; Foch, Nina.; Scott, Martha; 1914-2003.; Anderson, Judith; 1897-1992.; Price, Vincent; 1911-1993.; 1926-1998.; Carradine, John.; Derek, John; et al. (Hollywood, Calif., 2004)
Lavish Biblical epic that tells the life story of Moses from the time he was discovered in the bulrushes as an infant by the pharaohs daughter. As an adult, he turns his back on his privileged life in Egypt to lead his true people, the Hebrews, to freedom outside Egypt.
Paramount presents a Cecil B. DeMille production ; written for the screen by Aeneas MacKenzie ... [et al.] ; produced and directed by Cecil B. DeMille.
Keywords: Moses; (Biblical leader); Drama; Video recordings for the hearing impaired; Feature films; Religious films; Bible films; Drama; Epic films; To 1200 B.C.; History; Jews; Drama; Exodus, The; Feature films; Religious films; Bible films; Epic films